Behavioral Consequences of Alcohol Use Among Students of Isabela State University – Main Campus - Edmelyn B. Cacayan; Queenie B. Solatre; Mark Hipolito Placido Galingana (Humanistic Network for Science and Technology (HNST), 2020)
The study was focused on the behavioural consequences state of alcohol use among the students. The respondents were all levels of students of Isabela State University-Main Campus. The researcher used survey questionnaire and interview to gather data. The study found out that the majority of the respondents were under 19-20 years old, male, junior with allowance of 100-200 pesos per day. The Behavioral Consequences on Alcohol Use Among Students of Isabela State University-Main Campus were the following: First was the Profile of the Respondents, followed by the Awareness of the Respondents on Alcohol, Behavioral Consequences of Alcohol and lastly the Leading Factors on Using Alcohol. Based on the above conclusions, the following recommendations were: Clinicians are important to screen students of Isabela State University-Main Campus for alcohol misuse and provide persons engaged in risky or hazardous drinking with behavioral counselling interventions to reduce alcohol misuse. That those who do not consume alcoholic beverages should not start doing so because of the negative impact. Provide Educational Programs among Isabela State University-Main Campus students to enhance their knowledge about alcohol consumption. Since the majority of respondent were 19-20 years old, a similar study should be conducted regarding other possible behavioral consequences, awareness and factors on alcohol and should also be conducted with larger number of respondents. Keywords: behavioral consequences; alcohol use; students